Regional Head Of Women, Participation Or Exploitation? (The Phenomenon Of Airin-Ana And Haryanti In The Maelstrom Of Political Dynasties & Local Oligarchy) - Amalia Syauket (Eduvest - Journal of Universal Studies, 2021)
Pilkada after pilkada continue to roll and are still dwelling on the same pattern of problems from the previous Pilkada which actually experienced a significant increase in the journey of regional heads who came from the Political Dynasty. When viewed by gender, in the 2020 Simultaneous Pilkada it can be seen that 57 women = 10.7%, of which 29 are female candidates who are wives of the previous regional head. This qualitative research prioritizes secondary data sources with 4M writing techniques, namely Describing, Analyzing, Concluding and Describing the phenomenon of Airin Rachmy Diany as Mayor of South Tangerang, Ana Sophanah as Regent of Indramayu and Haryanti as Regent of Kediri who are in the vortex of political dynasties & oligarchy, with big questions. Is this a form of participation or exploitation? Based on this phenomenon, it can be concluded that both Airin Rachmy Diany and Ana Sophanah and also Haryanti have been exploited by oligarchs who are in-laws, or husbands in order to strengthen political dynasties and oligarchic networks in their respective regions, rather than in the form of political participation themselves. As a Regional Head, he is exploited for the defense industry his power is also correlated with the defense of wealth which makes him not independent in running the wheels of government in the region. The influence of male masculinity or family power still prevails in the government even if the position of the wife or daughter is higher than that of her father or husband as members of ordinary society.